PM.03 Relationship Between Fetal Growth, Cardiovascular Adaptation and Birth Weight. (26th April 2013) - Mahendru, AA; Everett, TR; McEniery, CM; Wilkinson, IB; Lees, CC
Abstract : Maternal cardiovascular adaptation in pregnancy is necessary for optimal fetal growth. The objective of this study was to explore the relationships between growth rate, fetal size at 10–14 weeks, birth weight and maternal cardiovascular adaptation in pregnancy. This was a prospective study of 143 women planning to conceive. Crown rump length (CRL) was measured in 71 viable pregnancies at 6–7, 8–9 and 10–14 weeks in 1 st trimester and biometry was performed at 22–24 and 32–34 weeks. First and 2 nd to 3 rd trimester growth rates were calculated. Cardiovascular assessments were performed pre-pregnancy, at 6–7 weeks, in 2 nd and 3 rd trimesters. We examined the relationships between 1 st trimester CRL growth rate, CRL z-score at 10–14 weeks, 2 nd to 3 rd trimester fetal growth rate, birth weight z-score and cardiovascular adaptation. First trimester fetal growth and CRL z-score were not related to 2 nd to 3 rd trimester fetal growth rate ( P = 0.2, P = 0.4) nor to birthweight z-score ( P = 0.5). However, 2 nd to 3 rd trimester fetal growth rate was positively correlated to birthweight z-score (ρ = 0.758, P < 0.001). Amongst the maximum cardiovascular changes the pre-pregnancy to 2 nd trimester increase in cardiac output (CO) was significantly correlated to birthweight z-score (ρ = –0.257, P = 0.03). Pregnancy induced cardiovascular changes by 2 nd trimester may 'drive' later pregnancy fetal growth and birthweight. Contrary to previous reports based on assumption of growth on a single CRL measurement at 10–14 weeks, birthweight was not related to 1 st trimester growth; but was related to 2 nd to 3 rd trimester fetal growth and maximum increase in CO by 2 nd trimester.